2017
DOI: 10.1155/2017/7190801
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Annealing Process on CH3NH3PbI3-XClX Film Morphology of Planar Heterojunction Perovskite Solar Cells with Optimal Compact TiO2 Layer

Abstract: The morphology of compact TiO 2 film used as an electron-selective layer and perovskite film used as a light absorption layer in planar perovskite solar cells has a significant influence on the photovoltaic performance of the devices. In this paper, the spin coating speed of the compact TiO 2 is investigated in order to get a high-quality film and the compact TiO 2 film exhibits pinhole-and crack-free films treated by 2000 rpm for 60 s. Furthermore, the effect of annealing process, including annealing temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…[7] Planar heterojunction P-I-N and N-I-P PSCs are promising structures compared with their counterpart mesoporous PSCs because of the high annealing temperature and additional processing difficulties required for preparing mesoporous TiO 2 . [8] Among different methylammonium lead halide perovskite, such as CH 3 NH 3 PbI 3 , CH 3 NH 3 PbBr 3 , and CH 3 NH 3 PbI 3Àx Cl x , the CH 3 NH 3 PbI 3Àx Cl x structure is more suitable for planar heterojunction PSCs, owing to its remarkable properties such as long diffusion lengths (L D ) for both holes and electrons [2,9,10] and an appropriate bandgap. [11] The L D of CH 3 NH 3 PbI 3 is about 100 nm; [5] however, it can be increased up to 1 μm upon the addition of chlorine (Cl) to form the CH 3 NH 3 PbI 3Àx Cl x structure.…”
mentioning
confidence: 99%
“…[7] Planar heterojunction P-I-N and N-I-P PSCs are promising structures compared with their counterpart mesoporous PSCs because of the high annealing temperature and additional processing difficulties required for preparing mesoporous TiO 2 . [8] Among different methylammonium lead halide perovskite, such as CH 3 NH 3 PbI 3 , CH 3 NH 3 PbBr 3 , and CH 3 NH 3 PbI 3Àx Cl x , the CH 3 NH 3 PbI 3Àx Cl x structure is more suitable for planar heterojunction PSCs, owing to its remarkable properties such as long diffusion lengths (L D ) for both holes and electrons [2,9,10] and an appropriate bandgap. [11] The L D of CH 3 NH 3 PbI 3 is about 100 nm; [5] however, it can be increased up to 1 μm upon the addition of chlorine (Cl) to form the CH 3 NH 3 PbI 3Àx Cl x structure.…”
mentioning
confidence: 99%
“…Moreover, it has been reported that ultrathin gold (Au) contact has better electrical conductivity as well as optical reflectance‐scattering to preserve the performance of the cell 56 . Chen et al 57 have also demonstrated the application of Au as a back contact in CH 3 NH 3 PbI 3−x Cl x ‐based solar cells. Due to these advantages of cSi and Au, we proposed these as an HTL and back contact in the proposed structures.…”
Section: Introductionmentioning
confidence: 99%
“…Heterojunctions are known to be the most competitive method of solar cell fabrication on account of being the simplest [36]. A P-N junction is created when P-type (NiO) and N-type (TiO 2 ) semiconductor materials are placed in contact with one another.…”
Section: Introductionmentioning
confidence: 99%